Parameterized steering criteria via correlation matrices - Qing-Hua Zhang; Lemin Lai; Shao-Ming Fei (Results in Physics, 2024)
We study the steerability for arbitrary dimensional bipartite systems based on the correlation matrices given by local special unitary groups. We present families of steering criteria for bipartite quantum states in terms of parameterized correlation matrices. We show that these steering criteria may detect more steerable states than the existing steering criteria. The results are illustrated by detailed examples.